Optimal protection coordination in the micro-grid including inverter-based distributed generations and energy storage system with considering grid-connected and islanded modes - Asl, Saeed Abrisham Foroushan; Gandomkar, Majid; Nikoukar, Javad (Electric power systems research, 2020)
•Modeling the optimal protection coordination strategy for grid-connected and islanded micro-grid based on the daily data of optimal operation of this network.•Considering RES and ESS simultaneously in the OPC method, where previous researches select only the constant capacity for DGs.•Investigating the impact of the energy management for DGs and ESS on the OPC using the protection coordination index.•Using reliable and secure solver such as CSA with low standard deviation in the large scale problem of the OPC method. This paper presents the optimal protection coordination (OPC) to grid-connected and islanded micro-grid (MG) consisting renewable energy sources (RESs), and energy storage system (ESS). The proposed approach considers objective function as minimizing the total operation time of the dual setting overcurrent relays (DSORs) in primary and backup protection mode. Problem constraints are the regulation parameters limits of the DSROs, sizing limit of FCLs and also the coordination time interval (CTI) inequality. MG includes generally RESs and ESS, hence, this problem needs to the daily optimal operation results of MG in both grid-connected and islanded modes to obtain the network variables before the fault occurrence. Therefore, it is minimized the MG operation and load shedding costs of islanded MG while it is constrained to MG optimal power flow equation in the presence of RESs and ESS. The proposed OPC includes non-linear model, hence, this paper uses the crow search algorithm (CSA) to obtain a reliable and optimal solution for this formulation. Finally, this strategy is implemented on the 9-bus and 32-bus MGs, thus, it can obtain the high quick protective solution for these MGs by selecting optimal regulation parameters and sizing to DSORs and FCLs, respectively, according to numerical results. [Display omitted]